Brazilian democracy’s in effectiveness in the face of the legal spoliation of Brazilaid [Auxílio Brasil] - Mol Eyer Lage, Matheus; Menezes de Oliveira, Camila (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
This paper seeks to understand, through the conceptual analysis of theideas of Frédéric Bastiat and Murray Newton Rothbard, the in effectiveness of Brazilian democracy in the face of legal spoliations contained in norms presented in the Brazilian legal system, especially in those affirmative actions related to the Bastiat’s concept of obligatory fraternity. In this sense, we look at the legal spoliation presented in Law 14.284/2021 that institutes the social program Auxílio Brasil. In conclusion, we argue that the role of Law is of great value in minimizing the possibility of property transfer from one person to another with legal backing by guaranteeing only natural rights.